2018
DOI: 10.1177/1474704917753857
|View full text |Cite
|
Sign up to set email alerts
|

Affection, Deception, and Evolution: Deceptive Affectionate Messages as Mate Retention Behaviors

Abstract: This study explored how partner mate value (PMV) and factors indicative of the relational climate (i.e., commitment and satisfaction) might affect individuals' tendency to use deceptive affectionate messages (DAMs). Participants ( N = 203) responded to a survey including measures regarding these variables. Contrary to predictions, PMV and the tendency to engage in DAMs were significantly and negatively associated with one another. Analyses further indicated that commitment significantly moderated the negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…The mate-retention motive aims to maintain a long-term relationship with a specific mate. This motive requires individuals to actively maintain existing relationships and eliminate potential relationship threats to prevent relationship breakdowns and loss of reproduction opportunities ( Redlick and Vangelisti, 2018 ). For example, individuals maintaining intimate relationships usually act more caring toward their partners ( Saad and Gill, 2003 ) and give lower appraisals to other potential relationship threats ( Lydon et al, 2003 ).…”
Section: Conceptualization and Hypothesesmentioning
confidence: 99%
“…The mate-retention motive aims to maintain a long-term relationship with a specific mate. This motive requires individuals to actively maintain existing relationships and eliminate potential relationship threats to prevent relationship breakdowns and loss of reproduction opportunities ( Redlick and Vangelisti, 2018 ). For example, individuals maintaining intimate relationships usually act more caring toward their partners ( Saad and Gill, 2003 ) and give lower appraisals to other potential relationship threats ( Lydon et al, 2003 ).…”
Section: Conceptualization and Hypothesesmentioning
confidence: 99%
“…Research showed DAMs were not associated with relational commitment or satisfaction, rather greater frequency of general deception was associated with less commitment and satisfaction (Gillen & Horan, 2013). Similarly, another study found that individuals perceiving high relational commitment were less likely to use DAMs (Redlick & Vangelisti, 2018). Thus, RSEs are similar to altruistic social lies and DAMs, in that they are often intended to benefit the receiver or the relationship rather than using a deceptive strategy to hide feelings or information.…”
Section: Deception In Close Relationshipsmentioning
confidence: 99%
“…Based on previous research (Caton & Horan, 2019; Horan & Booth-Butterfield, 2013; Redlick & Vangelisti, 2018), DAMs should first be triggered when the underlying evolved perceptual system detects a potential cue to relational threat—which is not the perceived threat itself, but the initial cue to the perceived threat (Barkow et al, 1992; Buss & Shackelford, 1997; Starratt & Shackelford, 2023)—including low partner commitment and satisfaction (Drigotas et al, 1999). While low satisfaction and commitment might not always trigger actual relational threat (Arriaga & Agnew, 2001; Choice & Lamke, 1999; also see Figures 1 and 5, wherein the correlation between perceived commitment and defection is −.54, suggesting some distinction between these two perceptions), evolution favoured perceptual systems that could detect reliable threat signals with above-chance accuracy (see Barkow et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of a high mate value partner, compared to a low mate value partner, is costly (Buss, 2000). DAMs might carry a small degree of risk (e.g., conflict, discovered deception; Horan & Booth-Butterfield, 2011) but the loss of a highly valued partner carries substantially more costs (Redlick & Vangelisti, 2018). In considering AET, DAMs might be expressed when the benefits (minus the costs) of expressing DAMs outweigh the benefits (minus the costs) of not using DAMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation